SSVEP BCI and Eye Tracking Use by Individuals With Late-Stage ALS and Visual Impairments - Peters, Betts; Bedrick, Steven; Dudy, Shiran; Eddy, Brandon; Higger, Matt; Kinsella, Michelle; McLaughlin, Deirdre; Memmott, Tab; Oken, Barry; Quivira, Fernando; Spaulding, Scott; Erdogmus, Deniz; et al. (Frontiers in Human Neuroscience, 2020)
Access to communication is critical for individuals with late-stage amyotrophic lateral sclerosis (ALS) and minimal volitional movement, but they sometimes present with concomitant visual or ocular motility impairments that affect their performance with eye tracking or visual brain-computer interface (BCI) systems. In this study, we explored the use of modified eye tracking and steady state visual evoked potential (SSVEP) BCI, in combination with the Shuffle Speller typing interface, for this population. Two participants with late-stage ALS, visual impairments, and minimal volitional movement completed a single-case experimental research design comparing copy-spelling performance with three different typing systems: 1) commercially-available eye tracking communication software, 2) Shuffle Speller with modified eye tracking, and 3) Shuffle Speller with SSVEP BCI. Participant 1 was unable to type any correct characters with the commercial system, but achieved accuracies of up to 50% with Shuffle Speller eye tracking and 89% with Shuffle Speller BCI. Participant 2 also had higher maximum accuracies with Shuffle Speller, typing with up to 63% accuracy with eye tracking and 100% accuracy with BCI. However, participants’ typing accuracy for both Shuffle Speller conditions was highly variable, particularly in the BCI condition. Both the Shuffle Speller interface and SSVEP BCI input show promise for improving typing performance for people with late-stage ALS. Further development of innovative BCI systems for this population is needed.